Perbedaan Nilai Kesegaran Punggung Sebelum dan Sesudah Pemberian Stretching Mc. Kenzie Extension pada PekerjaWanita Pengepak Jamu PT. X Semarang - Permana, Dinda Rizki; Wahyuni, Ida (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2010)
Every work has the potential on giving risk to health; one of them is caused by unnatural workingposition. As an example, for work that require their worker to do the work in sitting position potentiallygive a health risk such as complaint on musculoskeletal. Sitting work position that being done by theherbal medicine packager at PT.X Semarang for 8 working hours allows the occurrence of the unnaturalgesture. From short interview to 6 workers, there were 5 of them that complaint about the feeling of lesscomfortable/stiff on area around back and neck after work. Some studies said that by giving stretchingmovement can reduce this muscular complaint. Stretching Mc.Kenzie Extension is one of stretchingmethod that intended to strengthen the back. Back fitness value will show how well the back of a workerto work on a sitting position is. The goal of this study is to know the difference between back fitness valuebefore and after treatment of Stretching Mc.Kenzie Extension to PT.X Semarang herbal medicinepackager workwoman.This research is Quasi Experiment using One Group Time Series Design with amount of sample is 10peoples. The result tested with statistical paired T-test (Î± = 0,05) preceded with data normality test usingSaphiro Wilk test.The result showed tahat there was a difference between back fitness value before and after treatment ofStretching Mc.Kenzie Extension. Therefore, it is advised for the company to give knowledge to workerabout sitting position that meet ergonomic norm. Furthermore by doing design improvement on workfacilities such as work table and chair.Keywords: back fitness value, stretching Mc.Kenziehttp://ejournal.undip.ac.id/index.php/mkmi/article/view/2892Â